👤
Robus93
a fost răspuns

Imi puteti explica cum se fac?? pls
(3x+2y)(4x+5y)
(7x-4)
(2-x)(2+x)


Răspuns :

( 3 x + 2 y ) ( 4 x + 5 y ) =  12 x² + 23 x y + 10 y²

= 3 x · 4 x + 3 x · 5 y + 2 y · 4 x + 2 y · 5 y =

= 12 x² + 15 x y + 8 x y + 10 y² =

= 12 x² + 23 x y + 10 y²

___________________________

( 7 x - 4 )² = ( 7 x )² - 2 · 7 x · 4 + 4² = 49 x² - 56 x + 16

__________________________________________

( 2 - x ) ( 2 + x ) = 4 - x²

= 2 · 2 + 2 · x - 2 · x - x · x =

= 4 + ( 2 x - 2 x ) - x² =

= 4 - x²

..........................
Vezi imaginea Trombolistul